2017
DOI: 10.1136/bmjopen-2017-017517
|View full text |Cite
|
Sign up to set email alerts
|

Is overseas volunteering beneficial to the NHS? The analysis of volunteers’ responses to a feedback questionnaire following experiences in low-income and middle-income countries

Abstract: IntroductionLocally requested and planned overseas volunteering in low-income and middle-income countries by National Health Service (NHS) staff can have benefits for the host or receiving nation, but its impact on the professional development of NHS staff is not proven. The Knowledge and Skills Framework (KSF) and Leadership Framework (LF) are two tools used by employers as a measure of individuals' development. We have used dimensions from both tools as a method of evaluating the benefit to NHS doctors who v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
2
9
0
Order By: Relevance
“…As with previous studies of orthopaedic volunteers, 24 most hosts and volunteers in our study agreed that volunteers were able to gain skills through volunteering that they could apply at their home practices, indicating a bidirectional transfer of skills and knowledge between the host and volunteer. Previous authors have noted that international experiences often allow volunteers to expand their medical knowledge and improve their physical examination skills 9 because volunteers are often used to relying on technology that may be limited when practicing abroad.…”
Section: Bidirectional Learning and Reverse Innovationsupporting
confidence: 87%
“…As with previous studies of orthopaedic volunteers, 24 most hosts and volunteers in our study agreed that volunteers were able to gain skills through volunteering that they could apply at their home practices, indicating a bidirectional transfer of skills and knowledge between the host and volunteer. Previous authors have noted that international experiences often allow volunteers to expand their medical knowledge and improve their physical examination skills 9 because volunteers are often used to relying on technology that may be limited when practicing abroad.…”
Section: Bidirectional Learning and Reverse Innovationsupporting
confidence: 87%
“…17 Studies have reported that the experience of medical volunteering (undergraduate and postgraduate) can affect the individual volunteer personally and professionally, resulting in positive changes in world views, values and outlooks. [18][19][20][21][22][23][24] There is research exploring the experiences and perceived impact of healthcare providers who have volunteered in healthcare facilities providing a clinical service, although much of this research is low quality and largely anecdotal. To date, there is less research regarding the experiences and impact of healthcare providers, both from the UK and LMIC settings, who undertake short-term volunteer placements to teach and facilitate on maternal and newborn training workshops in low-resource settings.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Additionally, there is a growing body of academic literature reinforcing the merit of international health partnerships. 18,19 This corresponds with a substantial amount of support at both governmental and institutional levels, with multiple documents produced by a variety of official bodies. 12-17,20-25 Extensive high-level support, combined with potential benefits for host nations, trainees, and the wider NHS, represents driving forces for broadening the involvement of the UK T&O community with partnerships in LMICs.…”
Section: An Unquestionable Need: the Driving Forcesmentioning
confidence: 99%